Experimental Understanding of Ozone Decomposition inside a Low Temperature Combustion Engine. Issue 2 (25th January 2022) - Seignour, N.; Khacef, A.; Foucher, F.
ABSTRACT: Low-temperature combustion engines have the potential to meet pollutant requirements and reduce fuel consumption. The present study, based on an ultraviolet light absorption diagnostic, investigates ozone decomposition inside a single-cylinder compression ignition engine. Experiments were performed under HCCI conditions for non-reactive and reactive cases. Experimental results showed that intake parameters, pressure and temperature, and intake flow composition have a significant impact on ozone decomposition timing. In this study H2 O vapor and Isooctane seem to have the most significant impact on ozone decomposition.